Food Packaging Rebranding Assistance for Vegetable Products of OkeFarm Neglasari Women Farmer Group - Dimas Bayu Pinandoyo; Asriadi Masnar; Supardianningsih Supardianningsih (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Packaging is one of the aspects that affecting the trust of consumers to a product. As a small enterprise, OkeFarm Neglasari Women Farmer had no packaging expert. The aim of this community service is to provide a good packaging to help them gaining new consumers. The packaging rebranding, developed by market analysist methods and adjusted to the financial ability of the small enterprise. The finalized designs were tested to packaging acceptance test by mean questioner methods. Rebranding resulted 30 new loyal consumers, 25 of them responded to the questioners. 76% of the new consumers were females and 24% of it were males. Most of the new consumers were at age range 31-35 years old (44%) and 26-30 years old (36%). The rebranding effective to attract consumers with income range 3.1-6 million IDR (40%), and 6.1-9 million IDR (24%). The new food packaging brand significantly increased the acceptance of vegetables products.